Fundacje pokutne w Wielkopolsce w XIII-XV wieku - Piwek, Waldemar (Ecclesia. Studia z Dziejów Wielkopolski, 2009)
In the Middle Ages the relations between man and God were realized among others by means of material offerings which were a form of penance for committed sins and transgressions. Those were the so-called penitential foundations, donations or deeds of gift to the Church. One of the more important extra-religious aspects of penitential deeds of gift was the pursuit of a greater economic independence of the Church by obtaining and then confirming its economic immunities. Thanks to those foundations, for instance monasteries conducted large scale economic activities which were instrumental in the development of agrarian culture. The author focuses his studies on Wielkopolska, understood as the territory where the document was issued and as the place of permanent residence of the founder or the recipient of the foundation.